Addition of Essential Oil Bioadditives as a Mixture of Biodiesel B35 Fuel on the Performance of Reducing Water content and Particulate Content - Anggi Firdaus Agumsah; Meika Syahbana Rusli; Dwi Setyaningsih; Egi Agustian; Ade Kurniawan (The University of Lampung, 2023)
The use of biodiesel is still experiencing problems due to large amount of water content which produce from the transesterification process, making it has unstable oxidizing properties. The large amount of water content in biodiesel causes the emergence of microorganisms which becoming sludge in the engine room, and can clog the fuel filter. In this study, we propose the application of oxygenate bio-additives to minimize water and particulate content by using turpentine essential oils, clove terpenes, rhodinol, camphor oil, and synthetic additive 2EHN. Based on the study's results, the water content of biodiesel B35 with the AC bio-additive mixture experienced the highest decrease in water content, which was 18% or 287.2 ppm and performs well in reducing particulate levels of 4, 6, and 14 microns. The completely randomized design (CRD) test results for non-factorial moisture content on days 0, 3, 5, 7, and 14 and particulate matter 4, 6, and 14 microns showed no significant difference because each P value was obtained greater than α (0.05). Keywords: Bio-Additives, Biodiesel, Oxidation, Oxygenate, Particulates.